2001
DOI: 10.1007/s11627-001-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

in vitro propagation of Ochreinauclea missionis (Wall. EX G. Don), an ethnomedicinal endemic and threatened tree

Abstract: Biotechnology has offered a nonconventional method of plant propagation and has been intensively applied as a conservation strategy for sustaining biodiversity for rare plants. In vitro conservation through micropropagation of Ochreinauclea missionis, a rare, endemic and medicinal tree species of Western Ghats in Karnataka region of India is reported. Multiple shoots were initiated from nodal explants on Murashige and Skoog (MS) medium supplemented with 8.8 mM 6-benzylaminopurine (BA) and 0.3% (w/v) activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Possible reason for high phenol rate in spring and summer might be related to the new growth of shoots, which provides the possibility of phenol exudation. K Dalal and Rai (2001) and Bhatt and Dhar (2004) noted that explants taken during the winter season showed maximum bud break, which is contrary to the present report where the lowest rate of bud break was seen in winter season. Chaturvedi et al (2004) and Arora et al (2010) in neem plant, and Phulwaria et al (2012) in Terminalia catappa reported that explants taken in March and April showed maximum bud break which is not in line with the results of the present study, where the highest bud break rates were seen in October and November.…”
Section: Discussioncontrasting
confidence: 99%
“…Possible reason for high phenol rate in spring and summer might be related to the new growth of shoots, which provides the possibility of phenol exudation. K Dalal and Rai (2001) and Bhatt and Dhar (2004) noted that explants taken during the winter season showed maximum bud break, which is contrary to the present report where the lowest rate of bud break was seen in winter season. Chaturvedi et al (2004) and Arora et al (2010) in neem plant, and Phulwaria et al (2012) in Terminalia catappa reported that explants taken in March and April showed maximum bud break which is not in line with the results of the present study, where the highest bud break rates were seen in October and November.…”
Section: Discussioncontrasting
confidence: 99%
“…Although there are several studies on micropropagation from nodal segments (Nhut 1998;Dalal and Rai 2001;Arya et al 2003;Sharma et al 2003;Raghu et al 2006), the use of this type of explant for bromeliads has not been described; it has mostly been reported in the genus Ananas (Kiss et al 1995;Nievola et al 2005;). Nodal segments of A. strobilacea have a 100% regeneration rate in the absence of growth regulators (Souza et al 2003;.…”
Section: Discussionmentioning
confidence: 99%
“…In the framework of the scientific collaboration between the ICSN and the Universiti Malaya, our laboratories have embarked on a project to find IA scaffold using MN from Ochreinauclea maingayi, which belongs to the genus of Ochreinauclea (Rubiaceae). Throughout the world, there are only two species, O. maingayi and O. missionis, which are understudied in phytochemical analysis [6,7]. O. maingayi is a commercial timber that is mostly distributed in Peninsular Malaysia, Borneo, Sumatra, and Thailand [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…O. maingayi is a commercial timber that is mostly distributed in Peninsular Malaysia, Borneo, Sumatra, and Thailand [8,9]. The bark root of O. missionis, which is typically discovered in India, has been used to treat ulcers, fever, rheumatism, jaundice, edema, hepatitis, and haemophilia [6,7]. Prior phytochemical studies of the leaves of O. maingayi [10] revealed that indole alkaloids are the predominant compounds and are active towards vasorelaxant activities.…”
Section: Introductionmentioning
confidence: 99%